Optimization of the Growing Environment Through Applying Mulch and Liquid Organic Fertilizer on The Growth and Yield of Shallots (Allium ascalonicum L.) - Mirza Ayu; Sudiarso; Euis Elih Nurlaelih (Jurnal Ilmu Pertanian Indonesia, 2026)
Shallots (Allium ascalonicum L.) are widely consumed, but their productivity remains inconsistent due to various factors, including the long-term reliance on chemical fertilizers, which negatively impact soil and water quality. Therefore, sustainable cultivation strategies, including the application of liquid organic fertilizers (LOF) and plastic mulch, are needed. This study aimed to evaluate the interactive effects of different LOF concentrations (10–20 mL/-1) and black silver plastic mulch on the growth and yield of shallot plants. The research was conducted from November to January 2024 in the dryland of Dusun Kasin, Ampeldento Village, Karangploso Subdistrict, Malang Regency. This study employed a factorial randomized block design RBD method. In terms of growth parameters, mulch treatment (M1) at the LOF P20 concentration can increase 33.33% of root fresh weight, 12% of plant dry weight, 6.73% of leaf area and 6.86% of plant height compared to that without mulch. The results showed that mulch treatment at the LOF P20 concentration increased tuber fresh weight, 30.85% of tuber dry weight per clump, 14.16% of tuber shrinkage weight, and harvest yield by 24.13, 30.85, 14.16, and 19.44%, respectively. LOF P20 provided significantly higher yields than P0 in all treatments. Keywords: Black silver plastic mulch, liquid organic fertilizer, shallots